Factors influencing clothing interest and purchase intention: a study of Generation Y consumers in Malaysia - Cham, Tat Huei; Ng, Caryn Kar Yan; Lim, Yet Mee; Cheng, Boon Liat * (2017)
The purpose of this study is to examine the factors influencing clothing interest among Generation Y consumers in Malaysia. Brand image, word of mouth, self-concept, perceived quality, and need for uniqueness were hypothesized to be related with clothing interest, which in turn, was deemed to be related with purchase intention. The interaction effect of price consciousness on the relationship between clothing interest and purchase intention was also examined in this study. Self-administered questionnaires were used to collect data from a total of 300 respondents from Malaysia to test the hypothesized relationships. Results showed that need for uniqueness, self-concept, brand image, word of mouth, and perceived quality are significant predictors of clothing interest among the Generation Y consumers in Malaysia and price consciousness moderated the relationship between their clothing interests and purchase intention. The practical implications of the research findings were discussed.